Convergent spaces: Intersectional analysis of ethnic minority status and childhood disability in Irish safeguarding work - Flynn, Susan (My University, 2020)
The core argument of this paper is that intersectionality provides a constructive conceptual lens for the convergence of ethnic minority status and childhood disability in Irish child protection and welfare. The utility of intersectionality in this paper lies in broadening the scope of reflection on the complex intersections of ethnic minority status and childhood disability. Within this, intersectionality is implicitly situated within an overarching critical disability studies perspective. Theoretically informed commentary on the literature attends to three aspects of practice. These are respectively: novel intersections of ethnic minority status and childhood disability, as a consequence of intensifying globalisation; compounded levels of risk; and the importance of non-conflation of potential sites of oppression, such as race and disability. Overall, the intention of the paper is to be illustrative. Specifically, analysis is presented as an aid to students and practitioners, moving forward, in negotiating a complex and dynamic field of practice.
PUBLISHED
Keywords: Intersectionality; Ethnic minority; Disability; Children; Safeguarding; Child protection